2008
DOI: 10.1111/j.1755-263x.2008.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopian coffee cultivation—Implications for bird conservation and environmental certification

Abstract: Coffee cultivation plays a role in biodiversity alteration and conservation in much of the tropics. This is particularly so in Ethiopia, where coffee is an indigenous shrub and a major commodity in national and local trade. In southwestern Ethiopia, coffee (Coffea arabica, "highland coffee") is harvested from both forests (its natural habitat) and from within farmland where it is grown in small patches under isolated shade trees. We investigated the effects of management practices on bird assemblages in each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 33 publications
6
51
0
Order By: Relevance
“…In addition to planned biodiversity for shade coffee, associated 454 biodiversity such as ferns (Yeshitila, 2008), epiphytes (Hylander 455 and Nemomissa, 2008), and birds (Gove et al, 2008) (Mendez et al, 2010). 460 Generally, woody species richness in state-owned plantations 461 and smallholder farms in this study is comparable to traditional 462 polyculture and rustic coffee systems of Latin America, respectively 463 (Moguel and Toledo, 1999;Philpott et al, 2008).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…In addition to planned biodiversity for shade coffee, associated 454 biodiversity such as ferns (Yeshitila, 2008), epiphytes (Hylander 455 and Nemomissa, 2008), and birds (Gove et al, 2008) (Mendez et al, 2010). 460 Generally, woody species richness in state-owned plantations 461 and smallholder farms in this study is comparable to traditional 462 polyculture and rustic coffee systems of Latin America, respectively 463 (Moguel and Toledo, 1999;Philpott et al, 2008).…”
mentioning
confidence: 65%
“…agricultural land. In addition to our findings for woody species, 365 found many species of epiphytes and orchids 366 Nemomissa, 2008, 2009;Hylander et al, 2013), and bird species 367 (Gove et al, 2008) are maintained in semi-forest coffee systems. 368 However, other researchers (Schmitt et al, 2010b;Hundera et al, 369 2013a) found that lianas, herbs, shrubs and orchids were not well 370 conserved in coffee farms.…”
mentioning
confidence: 76%
“…However, the effectiveness of natural enemies in suppressing crop pests is influenced by processes at both local and landscape scales Chaplin-Kramer and Kremen, 2012;Tscharntke et al, 2012). Many studies show that the presence of different land-use types in the landscape, such as high tree density or cover of semi-natural habitats, can enhance the species richness of pest-controlling organisms or the natural pest control services across agricultural landscape (Bianchi et al, 2006;Rusch et al, 2013;Weibull et al, 2003;Gove et al, 2008;Clough et al, 2009), but results are not consistent. Some studies show higher predation from birds (Perfecto et al, 2004;Johnson et al, 2010) and arthropod natural enemies (Langellotto and Denno, 2004;Bianchi et al, 2006) on insect herbivores in complex habitats.…”
Section: Introductionmentioning
confidence: 97%
“…This mosaic of land-use types could influence the natural enemy abundance and the corresponding crop pest suppression services (Abate et al, 2000). For example, heterogeneous farmlands of southwestern Ethiopia harbor a rich bird fauna with about the same species richness of insectivorous birds as in the adjacent forests (Gove et al, 2013), even though the overall species richness increases with tree cover (Gove et al, 2008). In our study area, Engelen (2012) recorded an average of 58 bird species per homegarden and these included many insectivorous species indicating the potential for pest control in this landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies consider East and southern African tropical forests than West African forests, but work is emerging to support land-use planning in the region, and results largely conform to those found for West Africa. Agroforestry in Ethiopian and Tanzania supports less diversity than forests but more than other land uses (Gove et al 2008;Hemp 2006;Hall et al 2011;Negash et al 2012). …”
Section: Tropical Forestsmentioning
confidence: 99%